The challenge of stickiness in contributing to Sustainable Development Goals 2030 through zakat institutions in Malaysia - Mhd. Sarif, Suhaimi (Lembaga Zakat Negeri Kedah, 2019)
Stickiness occurs in policy, practice and attitude of organizations. Factors contributing to stickiness can be related to human and non-human factors in the organizations. More seriously the human factors related to attitude and commitment. In ensuring holistic economic and social development through United Nation’s Sustainable Development Goals 2030 with 17 goals, all entities, individuals and groups are required to work collectively and inclusively. Zakat institutions have been paying zakat to eight categories of recipients (asnaf) based on the guidelines outlined in Islam. Nevertheless, there is not much impact to the society and the economy. The divide between the rich and the poor is getting wider. This will lead to no sustainable development socially as well as economically. This study explores the views of zakat officers on the issues and challenges in making the society and the economy performed and sustained. The study uses semi structured personal interview with the informants. The results of the interview argued that bureaucratic thinking, process and attitude contribute to lack of sustainability in the development of the society and the economy. The informants suggest for transformation on the bureaucratic thinking and attitude at zakat institutions in Malaysia.